(untitled) (BIS Humanities and Social Science, 2026)
Migrant students in Indonesia often face adaptation challenges due to cultural differences, one of which is communication culture shock. This study aims to understand the culture shock experienced by students from Kuantan Singingi Regency in Yogyakarta, as well as to analyze their communication strategies from the perspective of Communication Accommodation Theory. According to Howard Giles’ Communication Accommodation Theory, the inability to adapt communication methods (convergence) or the tendency to overly maintain identity (divergence) can increase social distance and trigger conflict. If left unaddressed, this situation can negatively impact students’ mental health, academic achievement, and social integration in their new environment. Using a qualitative method with an interpretive paradigm, data were collected through in-depth interviews with members of the Riau Students Association of Yogyakarta, Kuantan Singingi Commissariat (IPRY-KKS). The results indicate that culture shock manifests specifically through language barriers, misunderstandings due to the intonation of the Kuantan Singingi Melayu dialect which is perceived as more assertive, and disorientation towards local social norms such as the use of cardinal directions. In response, students dynamically apply two accommodation strategies. The convergence strategy, such as softening their voice and using basic Javanese vocabulary, is employed in public spaces to gain social acceptance. Conversely, the divergence strategy, which involves intentionally maintaining their native dialect, is used within the IPRY-KKS community to reinforce group identity and solidarity. The choice between these two strategies is influenced by contextual factors, interlocutors, and communication goals. This study concludes that Kuantan Singingi students are strategic communicators who actively navigate their new cultural environment, not only as an effort to survive but also to affirm their cultural identity.